Nonlinear Direct Torque Control of Interior Permanent Magnet Synchronous Motor Drive - Justo, Jackson J.; Mwasilu, Francis (Tanzania Journal of Engineering and Technology, 2019)
This paper presents a nonlinear direct torque control (NDTC) strategy of interior permanent magnet synchronous motors (IPMSMs) for electric vehicle (EV) propulsion. The proposed NDTC scheme applies a nonlinear model of IPMSM to dynamically determine the optimal switching states that optimize the EV drivers ' decision to reduce the workload. Moreover, the proposed NDTC method has a simple control structure and can explicitly handle system constraints and nonlinearities. The performance evaluation is conducted via a prototype IPMSM test-bed with a TMS320F28335 DSP. Comparative experimental results provide the evidence of improvements of the proposed NDTC strategy over the conventional DTC strategy by indicating a fast torque response and an accurate speed tracking even under rapid speed change conditions. Keywords: Direct torque control (DTC), interior permanent magnet synchronous motor (IPMSM), nonlinear direct torque control (NDTC).